2015
DOI: 10.1016/j.ijsu.2014.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory diseases of the non-lactating female breasts

Abstract: Idiopathic granulomatous mastitis is an uncommon inflammatory disease of the non-lactating breast. The combination of limited surgical treatment and systemic prednisolone given for 6 months effectively controls the disease as well as prevents recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 11 publications
1
8
0
1
Order By: Relevance
“…This study describes the epidemiology, clinical aspects, diagnostics, management, and etiological agents of reported NLIM and compares subjects regarding their country's GNI per capita. Female patients of reproductive age are the most affected by NLIM (17,72), and only a few reviews have reported cases in men (73,74). In terms of age and sex distribution, the findings in this study coincide with the prevalence reported (92.9% female) in a study on breast tuberculosis in the Republic of Togo (73).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This study describes the epidemiology, clinical aspects, diagnostics, management, and etiological agents of reported NLIM and compares subjects regarding their country's GNI per capita. Female patients of reproductive age are the most affected by NLIM (17,72), and only a few reviews have reported cases in men (73,74). In terms of age and sex distribution, the findings in this study coincide with the prevalence reported (92.9% female) in a study on breast tuberculosis in the Republic of Togo (73).…”
Section: Discussionsupporting
confidence: 87%
“…The incidence and prevalence of NLIM are challenging to estimate since most studies are published on lactational mastitis, and those regarding NLIM have several limitations in their methodology. The highest prevalence of NLIM occurs in women of reproductive age, whether breastfeeding or not (17)(18)(19). Males of any age can be affected as well (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Breast abscess could also be consequences of nonlactational diseases. The causes of nonpuerperal breast abscess are mostly involved with periductal mastitis and granulomatous lobular mastitis . Technically, it is absolutely feasible to perform such a surgery on patients with nonlactational breast abscess.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the risk of breast cancer in women increased significantly as the occurrence of non-lactational mastitis increased. Non-lactational mastitis is known to be related to chronic inflammation secondary to infection-induced cytokines 30 , as well as inflammatory, infectious, hormonal and autoimmunity factors 31,32 . Reportedly, the presence of exogenous and endogenous pathogen-associated molecular patterns (PAMPs) (bacteria, viruses and fungi, as well as endogenous molecules released from injured or dying cells) can cause the activation of inflammatory pathways 33 .…”
Section: Discussionmentioning
confidence: 99%